AN INVESTIGATION INTO ENGLISH AND VIETNAMESE RADIO NEWS TRANSCRIPTS - Võ Thị Kim Thoa (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study is originated in a wish to produce side by side comparisons of some linguistic features in Macrostructures and Microstructures of English radio news transcripts and Vietnamese radio news transcripts in a systematic way. The study focuses on analysing and comparing the lead and the structure of English radio news and Vietnamese radio news in terms of the Macrostructures. The syntactic features and lexical choice will be exploited in terms of Microstructures. From the description as well as a full analysis on distinguishing features, we will draw their differences and similarities and their frequencies of occurrence. It is hoped that the results of the study will be an access for a profound understanding of radio messages. The study will also make a certain contribution helping learners to achieve the linguistic competence in both languages and create favorable conditions for those who want to understand more about the radio language.